Faktor agen, pejamu, dan lingkungan kejadian obesitas pada anak usia 5-6 tahun - Pavilianingtyas, Astuti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background: The prevalence of obesity on children is significantly increasing in both of developing and developed countries and has negative impacts on their growth and development. The purpose of this study was to explain the factors that may influence obesity on children aged 5-6 years.Methode: The case-control study conducted from November 2016 – February 2017 in 7 Kindergartens and Elementary Schools in Tlogosari Kulon Village, Semarang to 88 students and their mother as respondents. The sampling method was proporsionate simple random sampling. The data collected using structured interview, questionnaires and supported by in-depth interview. Statistical analysis was conducted using multiple regression logistic method by SPSS 13.0.Results: The results of the study proved that frequency of fast food consumption ≥ 3 times per week (OR 3,8; 95%CI 1,316-11,161)[1], duration of screen time > 2 hours per day (OR 5,9; 95%CI 1,422-24,628), having minimum one obesity parent (OR 3,8; 95%CI 1,197-11,907) as the risk factors of obesity on children aged 5-6 years. Children aged 5-6 years who have ethnic background as Javanesse (OR 0,03; 95%CI 0,002-0,547) and mother with low-level education (OR 0,18; 95%CI 0,035-0,95) proved as protective factors of obesity.Conclusion: The obesity on children age 5-6 years was influenced by frequency of fast food consumption, duration of screen time, parent’s obesity, ethnic background and education level of mother. The influence of screen time and ethnic background on obesity in children need to extend as future epidemiological study.